Integrative systems immunology uncovers molecular networks of the cell cycle that stratify COVID‐19 severity. Issue 2 (13th January 2023) - Prado, Caroline Aliane de Souza; Fonseca, Dennyson Leandro M.; Singh, Youvika; Filgueiras, Igor Salerno; Baiocchi, Gabriela Crispim; Plaça, Desirée Rodrigues; Marques, Alexandre H. C.; Dantas‐Komatsu, Raquel Costa Silva; Usuda, Júlia N.; Freire, Paula Paccielli; Salgado, Ranieri Coelho; Napoleao, Sarah Maria da Silva; et al.
Abstract: Several perturbations in the number of peripheral blood leukocytes, such as neutrophilia and lymphopenia associated with Coronavirus disease 2019 (COVID‐19) severity, point to systemic molecular cell cycle alterations during severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) infection. However, the landscape of cell cycle alterations in COVID‐19 remains primarily unexplored. Here, we performed an integrative systems immunology analysis of publicly available proteome and transcriptome data to characterize global changes in the cell cycle signature of COVID‐19 patients. We found significantly enriched cell cycle‐associated gene co‐expression modules and an interconnected network of cell cycle‐associated differentially expressed proteins (DEPs) and genes (DEGs) by integrating the molecular data of 1469 individuals (981 SARS‐CoV‐2 infected patients and 488 controls [either healthy controls or individuals with other respiratory illnesses]). Among these DEPs and DEGs are several cyclins, cell division cycles, cyclin‐dependent kinases, and mini‐chromosome maintenance proteins. COVID‐19 patients partially shared the expression pattern of some cell cycle‐associated genes with other respiratory illnesses but exhibited some specific differential features. Notably, the cell cycle signature predominated in the patients' blood leukocytes (B, T, and natural killer cells) and was associated with COVID‐19 severity and disease trajectories. These results provide a unique global understanding of distinct alterations in cell cycle‐associated molecules in COVID‐19 patients, suggesting new putative pathways for therapeutic intervention.